Gender and Higher Education: Increasing Exposure of Harassment and Pay Gaps - Hazelkorn, Ellen (International Higher Education, 2018)
In Ireland and the United Kingdom, public discourse around issues of sexual harassment and promotion and pay gaps is increasing. A lack of research, combined with a lack of understanding, means the full scale is unknown, and universities lack basic guidelines. Narrow definitions of excellence also shape academic culture. But action is slowly taking hold. The take-away is that nothing moves institutions faster than compliance and money.